Kröhnke pyridines: Rapid and facile access to Mcl-1 inhibitors. Issue 10 (1st June 2018) - Conlon, Ivie L.; Van Eker, Daniel; Abdelmalak, Sameh; Murphy, William A.; Bashir, Hassan; Sun, Michael; Chauhan, Jay; Varney, Kristen M.; Godoy-Ruiz, Raquel; Wilder, Paul T.; Fletcher, Steven
Graphical abstract: Abstract: The tumorigenic activity of upregulated Mcl-1 is manifested by binding the BH3 α-helical death domains of opposing Bcl-2 family members, neutralizing them and preventing apoptosis. Accordingly, the development of Mcl-1 inhibitors largely focuses on synthetic BH3 mimicry. The condensation of α-pyridinium methyl ketone salts and α, β-unsaturated carbonyl compounds in the presence of a source of ammonia, or the Kröhnke pyridine synthesis, is a simple approach to afford highly functionalized pyridines. We adapted this chemistry to rapidly generate low-micromolar inhibitors of Mcl-1 wherein the 2, 4, 6-substituents were predicted to mimic the i, i + 2 and i + 7 side chains of the BH3 α-helix.